Good Things Come to Those Who Wait: The Importance of Professional Development for the Implementation of Differentiated Instruction - Gheyssens, Esther; Consuegra, Els; Engels, Nadine; Struyven, Katrien (Frontiers in Education, 2020)
Differentiated Instruction (DI) is proposed as an approach to create inclusive classrooms. Research shows that professional development is necessary for teachers to implement DI efficiently. This study investigates the effectiveness of a professional development programme (PDP) aimed at strengthening the DI competences of teachers. A quasi-experimental design consisting of a pre-test, post-test and control group was used to study the impact of the programme on teachers’ self-reported differentiated philosophies and practices. Questionnaires were collected from the experimental group (n = 284) and the control group (n = 80). Pre- and post-test results were compared using a repeated measure, ANOVA. Additionally, interviews with a purposive sample of teachers (n = 8) were conducted to explore teachers’ experiences of the PDP. The results show that the PDP was not effective in changing teachers’ DI competences. Multiple explanations are presented for the lack of improvement such as treatment fidelity, the limitations of instruments and the necessary time investment that change requires. The significance of this study lies in the bridge between the quantitative and qualitative results of the PDP. Moreover, this study exposes the complexity of research on professional development.